Fiscal decentralization, tax competition, and federal tax administration: a note from the Argentine experience - Piffano, Horacio Luis Pablo (2004)
The paper analyses the usual arguments discussed in the fiscal federalism literature about fiscal decentralization through normative and positive (public choice) approaches. Afterwards, limits to enhance significantly fiscal decentralization in countries with important regional asymmetries like Argentina are analyzed. Finally, the author suggests the necessity of a fiscal institutional reform, which allows an efficient and responsible vertical coordination. A superlative role is assigned to the federal revenue administration in the suggested reform.